Connecting Networks Companion Guide / Cisco Networking Academy - Graziani Rick; Vachon Bob (Pearson, 2014)
The official supplemental textbook for the Connecting Networks course in the Cisco Networking Academy CCNA Routing and Swtching curiculum. Introduction, Hierachical Network Designs, Connecting the WAN, Point-to-Point Connections, Frame Relay, Network Address Translation for IPv4, Broadband Solutions, Securing Site-to-Site Connectivity, Monitoring the Network, Troubleshooting the Network, Answers to the Check Your Understanding Questions.